2021
DOI: 10.1016/j.ijid.2020.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, HCV and HBV in Central Asia and the Caucasus: A systematic review

Abstract: Background: Human immunodeficiency virus (HIV), hepatitis C virus (HCV) and hepatitis B virus (HBV) are substantial public health threats in the region of Central Asia and the Caucasus, where the prevalence of these infections is currently rising. Methods: A systematic review of MEDLINE, Embase and PsycINFO was conducted with no publication date or language restrictions through October 2019. Additional data were also harvested from national surveillance reports, references found in discovered sources, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
1
31
1
1
Order By: Relevance
“…Clinico-demographic characteristics of donors, recipients, and outcomes were described in this paper. Our data showed that the main cause of ESLD among our patients was HBV, which accords with a systematic review indicating that Kazakhstan has the highest prevalence of HBV in central Asia [ 9 ]. Among a total of 64 liver transplantations, 53 recipients received a liver graft from living donors.…”
Section: Discussionsupporting
confidence: 91%
“…Clinico-demographic characteristics of donors, recipients, and outcomes were described in this paper. Our data showed that the main cause of ESLD among our patients was HBV, which accords with a systematic review indicating that Kazakhstan has the highest prevalence of HBV in central Asia [ 9 ]. Among a total of 64 liver transplantations, 53 recipients received a liver graft from living donors.…”
Section: Discussionsupporting
confidence: 91%
“…In the former Soviet countries, tuberculosis, drug use, and HIV infection were major public problems ( 50 52 ), which probably generated the pronounced increasing trends observed in Georgia, Armenia, and Kazakhstan. For example, a high prevalence of HIV was reported among IDU (>30%) in Kazakhstan ( 53 ). Furthermore, 35.8% of people living with HIV did not report good health-related quality of life, and the adverse factors included depression, coinfection with tuberculosis, and sexually transmitted diseases ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…A parallel review reported 8% prevalence of HBV among PWID living with HIV, pooled from 11 studies [42]. A review focusing on Central Asia and Caucasus found a wide variation in HBV (2.8-79.7%, 10 studies) and HIV (0-30.1%, 26 studies) prevalence among PWID [43].…”
Section: Prevalence Of Sexual Risk and Sexually Transmitted Infectionsmentioning
confidence: 99%